EFFICIACY OF MINIMALLY INVASIVE SURGERY ON HALLUX VALGUS : A SYSTEMATIC REVIEW - Susilo, Dhanang (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: The terms "Hallux valgus" or "hallux abducto-valgus" are the medical terms most commonly used in relation to a bunion anomaly. These deformities can result from foot or joint abnormalities, but the most common cause is wearing too-small or too-large shoes. High heels cause the body to bend forward, which puts pressure on the toes. The type of surgery depends on the bones involved, their angular connection, the joint injury, and other deformities. The aim: This article describe about efficiacy of minimally invasive surgery on hallux valgus. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 89 articles, whereas the results of our search on SagePub brought up 62 articles. The results of the search conducted for the last year of 2013 yielded a total 33 articles for PubMed and 17 articles for SagePub. In the end, we compiled a total of 19 papers, 12 of which came from PubMed and seven of which came from SagePub. We included seven research that met the criteria. Conclusion: MIS measures for HV surgery can be considered effective with a reoperation rate of less than 20%. Both the radiological and clinical outcome of the minimally invasive osteotomy and the open method are on par with one another.